The National School Headteacher Evaluation System is finally underway - Cianfriglia, Licia (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The article describes the introduction of the national school headteacher evaluation system in Italy, outlined in Ministerial Decree No. 47 of 12 March 2025. After years of attempts, a system has finally been established that links evaluation to performance-related pay. The system aims to improve the quality of education by enhancing leadership, based on measurable objectives and a transparent process. The evaluation takes into account both individual performance and the specific context, with the aim of promoting accountability and effectiveness in school management. The article illustrates the characteristics of the new model, the implementation timetable and the procedures for cross-examination and guarantees, emphasising the importance of training and monitoring for the success of the system.